Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Dinamika Multi Finance Bogor - Marwah Handayani; Muhamad Azis Firdaus; Hannisa Rahmaniar Hasnin (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2024)
This research was conducted at PT. Adira Dinamika Multi Finance Bogor. The purpose of this research is to determine the influence of leadership and work motivation on employee performance at PT. Adira Dinamika Multi Finance Bogor. This research is quantitative. The sample population in this research is all 58 employees. The data collection technique is by distributing questionnaires to all employees, then the data is processed using the Smartpls 4.0 application with the SEM (Structural Equation Modeling) Analysis method. The results obtained from the influence of leadership on employee performance with an original sample value of 0.266, T statistics 2.446 > 1.96 and P-values 0.007 < 0.05 mean that there is a positive and significant influence between leadership on employee performance. The results obtained from the influence of work motivation on employee performance with original sample results of 0.678, T statistics 6.609 > 1.96 and P-values 0.000 < 0.05 mean that there is a positive and significant influence between work motivation and employee performance. The results obtained from the influence of leadership on work motivation with an original sample value of 0.869, T statistics 16.878 and P-values 0.000 < 0.05 means that there is a positive and significant influence between leadership and work motivation. The results obtained from the influence of leadership on employee performance through work motivation with an original sample value of 0.589, T statistics 5,793 > 1.96 and P-values 0.000 < 0.05 mean that there is a positive and significant influence between leadership on employee performance through work motivation.